Wound irrigation and peritoneal lavage with antiseptic/antibiotic solution before wound closure during gastrointestinal surgery: a systematic review and meta-analysis - Motoi Uchino; Koji Tamura; Shinsuke Nomura; Seiichi Shinji; Keita Kouzu; Hiroji Shinkawa; Tomohiro Ishinuki; Toru Mizuguchi; Hiroki Ohge; Seiji Haji; Junzo Shimizu; Yasuhiko Mohri; et al. (BMC Surgery)
Abstract Background Surgical site infections (SSIs) can affect mortality, morbidity, and medical costs. Although it has recently been reported that washing with antiseptic/antibiotic solution can prevent SSI in clean surgery, the clinical impact in gastrointestinal surgery is still uncertain. Therefore, we performed a systematic review and meta-analysis to evaluate the efficacy of antiseptic/antibiotic solution during wound irrigation or peritoneal lavage in gastroenterological surgery. Methods The database search used PubMed, MEDLINE, and Cochrane Library. The following inclusion criteria were set for the systematic review. 1) Studies comparing with or without antiseptic/antibiotic irrigation/lavage during gastrointestinal surgery. 2) Studies that described surgical site infections and adverse events. 3) Studies conducted after 2000. Results A total of 8 randomized controlled studies (RCTs) and 3 observational studies were included in this meta-analysis. Three RCTs of wound irrigation with povidone iodine (PVI) solution revealed no significant difference between the PVI and control groups [RR 1.41, 95% CI (0.92 to 2.17): p = 0.69]. Three RCTs of peritoneal lavage with antibiotic solution showed no significant difference between the interventional group and control groups [RR 0.39, 95% CI (0.10 to 1.55): p = 0.18]. Regarding other antiseptic or antibiotic solutions, the number of studies and participants were too small for evaluation. Conclusion Wound irrigation and peritoneal lavage with antiseptic/antibiotic solution did not have enough efficacy for preventing SSI during gastroenterological surgery.